Karakteristik Sensori dan Kandungan Gizi Susu Fermentasi Berbasis Kedelai dan Madu - Sri Desfita; Wulan Sari; Yusmarini Yusmarini; Usman Pato (Jurnal Kesehatan Komunitas, 2023)
The study aimed to examine the effect of the types of bacteria and honey concentration on sensory characteristics and consumer preference levels on fermented soymilk and honey, as well as evaluate the nutritional content. This research was conducted between October and December 2019 at the Faculty of Agriculture, Riau University, and STIKes Hang Tuah Pekanbaru.  Laboratory experiment-based research used forest honey from Bengkalis Regency (Rupat honey). The descriptive test was carried out by 30 semi-trained panelists and the hedonic test was conducted by 100 untrained panelists. Determination of nutrient composition was performed by proximate analysis. The statistical method used the ANOVA test and continued with Duncan New Multiple Range Test (DNMRT) at a significance level of 5% to determine the differences among treatments. The result of the descriptive test showed that the type of bacteria, honey concentration, as well as the interaction between the bacteria and honey concentration, affected the sensory characteristic of fermented soymilk honey. The result of the overall hedonic test suggested that panelists preferred fermented soymilk honey using Lactobacillus casei subsp. casei R-68 to fermented soymilk honey using Lactobacillus plantarum 1 R. 1.3.2., with scores of 2.88 and 2.75 respectively. Overall panelists rather liked fermented soymilk honey. The taste of fermented soymilk honey needs to be improved through further research.